Effects of Moderate Exercise Training On ApoE And ApoCIII In Metabolic Syndrome - Ertekin, Kutluhan; Baştuğ, Metin; Gökçay Canpolat, Asena (European Journal of Therapeutics, 2023)
Introduction: Metabolic syndrome (MetS) is an endocrinopathy with a combination of cardiovascular and metabolic compounds. In our study, it is expected to obtain results showing that mortality rate, loss of workforce, and treatment costs due to disorders caused by MetS can be reduced by physical exercise. The study analyses the effect of moderate exercise training on this Apolipoprotein E (ApoE), Apolipoprotein CIII (ApoCIII), adiponectin, resistin, interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) which are thought to have a role in the deterioration of glucose and lipid metabolism in MetS. Methods: This clinical experimental study consists of 3 groups. The MetS+E (n=24) group, which included the participants who agreed to participate in the exercise program in addition to their medical treatment, the MetS (n=23) group who received medical treatment but did not exercise, and the Control+E (n=25) group, which included healthy volunteers who had the same protocol as MetS+E ApoE, ApoCIII, adiponectin, resistin, IL-6, and TNF-α plasma levels of all participants were measured both at the beginning of the study and at the end of the protocol. Results: At the end of the study we reached the following findings; insulin and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) levels decreased in exercise groups (p=0,03). ApoCIII levels increased in all the groups after the study (p<0,01). IL-6 levels decreased in MetS+E (p<0,01) and Control+E (p=0,037). ApoE (p=0,01) and TNF-α (p=0,037) levels decreased only in the Control+E group. Conclusion: Training showed metabolic, anti-inflammatory, and physical improvements independent of ApoE and ApoCIII in those with MetS.